ANN-Based Estimation of Groundwater Quality Using a Wireless Water Quality Network - Yılmaz Kılıçaslan; Gurkan Tuna; Gülsüm Gezer; Kayhan Gulez; Orhan Arkoc; Stelios M. Potirakis (International Journal of Distributed Sensor Networks)
Water is essential for life. Considering its importance for humans, it must be periodically analyzed to ensure its quality. In this study, a wireless water quality network is deployed to collect water quality parameters periodically and an artificial neural network-based estimation method is proposed to estimate groundwater quality. Estimating groundwater quality enables the authorities to take immediate actions for ensuring water quality. Compared to traditional water quality analysis methods, the proposed method has the advantage of letting the authorities know the quality of their water resources beforehand. A set of simulation studies given in this paper proves the efficiency and accuracy of the proposed method.